Pengaruh Pengetahuan Ibu dan Peran Petugas Kesehatan Terhadap Konsumsi Vitamin A pada Ibu Nifas di Wilayah Kerja Puskesmas Indrapuri Aceh Besar Tahun 2022 - Martina Martina; Yuli Zuhkrina (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2023)
During the postpartum recovery and breastfeeding process, postpartum mothers should get 2 capsules of vitamin A. Provision of vitamin A capsules for postpartum mothers can increase the amount of vitamin A in breast milk and help restore the mother's health, so giving 200,000 units of vitamin A capsules to postpartum mothers is very important. The coverage of giving vitamin A to postpartum women at the Indrapuri health center is 58% or 271 people of the target number of 100% (463 people). This study was to determine the effect of maternal knowledge and the role of health workers on vitamin A consumption in postpartum mothers. The method in this research is descriptive analytic research with a cross sectional approach. The population in this study were all postpartum mothers in the working area of ​​the Indrapuri Public Health Center in October-November 2022, namely 75 postpartum mothers. The sampling technique is total sampling. The results showed that there was an effect of mother's knowledge (P Value 0.045) and the role of health workers (P Value 0.020) on vitamin A consumption in postpartum mothers. It can be concluded: there is an influence of mother's knowledge and the role of health workers on vitamin A consumption in postpartum mothers. It is hoped that health workers, especially midwives, can monitor during postpartum visits to postpartum mothers and increase mothers' motivation by providing counseling about the importance of consuming vitamin A capsules during the postpartum period.